Cognitive processing load during listening is reduced more by decreasing voice similarity than by increasing spatial separation between target and masker speech - Zekveld, Adriana A.; Rudner, Mary; Kramer, Sophia E.; Lyzenga, Johannes; Rönnberg, Jerker (Frontiers in Neuroscience, 2014)
We investigated changes in speech recognition and cognitive processing load due to the masking release attributable to decreasing similarity between target and masker speech. This was achieved by using masker voices with either the same (female) gender as the target speech or different gender (male) and/or by spatially separating the target and masker speech using HRTFs. We assessed the relation between the signal-to-noise ratio required for 50% sentence intelligibility, the pupil response and cognitive abilities. We hypothesized that the pupil response, a measure of cognitive processing load, would be larger for co-located maskers and for same-gender compared to different-gender maskers. We further expected that better cognitive abilities would be associated with better speech perception and larger pupil responses as the allocation of larger capacity may result in more intense mental processing. In line with previous studies, the performance benefit from different-gender compared to same-gender maskers was larger for co-located masker signals. The performance benefit of spatially-separated maskers was larger for same-gender maskers. The pupil response was larger for same-gender than for different-gender maskers, but was not reduced by spatial separation. We observed associations between better perception performance and better working memory, better information updating, and better executive abilities when applying no corrections for multiple comparisons. The pupil response was not associated with cognitive abilities. Thus, although both gender and location differences between target and masker facilitate speech perception, only gender differences lower cognitive processing load. Presenting a more dissimilar masker may facilitate target-masker separation at a later (cognitive) processing stage than increasing the spatial separation between the target and masker. The pupil response provides information about speech perception that complements intelligibility data.